2003
DOI: 10.5194/aab-46-227-2003
|View full text |Cite
|
Sign up to set email alerts
|

Values of plasma lipid hydroperoxides and total antioxidant status in healthy dairy cows: preliminary observations

Abstract: Metabolic parameters have been used in an attempt to monitor the health, reproductive and nutritional status of dairy cows. Nevertheless, in the last few years the detection of free radical damage, and the protection against it has become very important in the practice of clinical medicine. This report aims to establish values for plasma lipid hydroperoxides (LOOH) and total antioxidant status (TAS) in healthy cows and its relationship with milk yield. The study was carried out with 22 healthy dairy cows divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
48
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 16 publications
7
48
0
3
Order By: Relevance
“…This implied that also the plasmatic a-toc levels in the calves of multiparous cows after birth were significantly higher, probably because of a higher a-toc transfer via placenta or a-toc secretion in the colostrum. Castillo et al (2005) reported that TAS obtained in late lactation and pregnant cows was lower than the one observed in a previous report on dairy cows at their lactation peak (Castillo et al, 2003), and these results were in agreement with Wachter et al (1999), which observed a progressive decline in antioxidant activity as lactation progresses, probably because of the depletion of fat-soluble antioxidants by milk.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This implied that also the plasmatic a-toc levels in the calves of multiparous cows after birth were significantly higher, probably because of a higher a-toc transfer via placenta or a-toc secretion in the colostrum. Castillo et al (2005) reported that TAS obtained in late lactation and pregnant cows was lower than the one observed in a previous report on dairy cows at their lactation peak (Castillo et al, 2003), and these results were in agreement with Wachter et al (1999), which observed a progressive decline in antioxidant activity as lactation progresses, probably because of the depletion of fat-soluble antioxidants by milk.…”
Section: Discussionsupporting
confidence: 89%
“…Our results, considered in the light of the available literature by Wachter et al (1999) and Castillo et al (2003), show a progressive decrease of serum antioxidants in Brown cows with the progress of lactation (from the 12th to the 16th day postpartum), probably because of the depletion of fat-soluble antioxidants by milk.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In milk, urea nitrogen forms 2.5-3 % of total nitrogen (Melendez et al 2000). Several experiments (Hamann & Kromker 1997, Skrzypek 1998, Castillo et al 2003 showed that in terms of nutrition, the optimum milk urea concentration for large dairy breed cows is 15-30 mg/dl. Monitoring blood or milk urea content may help to identify reasons for reproductive failure or health disorders (Markiewicz 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Because of passive diffusion, the urea molecule regulates concentrations of body fluids, and serum and milk urea levels are positively and highly correlated (Butler et al 1996, Castillo et al 2003. In milk, urea nitrogen forms 2.5-3 % of total nitrogen (Melendez et al 2000).…”
Section: Introductionmentioning
confidence: 99%